Development Of A High Sensitive Sandwich Elisa For Measuring Erythropoietin In Human Serum (Applied Biological Research, 2015)
The present paper describes a sandwich non-competitive enzyme-linked  immunosorbant assay (ELISA) for erythropoietin (EPO). The ELISA  utilizes a specific polyclonal antibody raised in rabbit against human  recombinant EPO (rhu EPO). Anti-EPO was coated onto 96-well micro titer plate, standard EPO or samples were added and left to bind to this  catching antibody. This was followed by the addition of same antibody,  which was conjugated with horse-radish peroxidase (HRP); and the  enzyme reaction developed was measured at 450 nm. Recombinant human  EPO was standardized against WHO 2nd International Reference  Preparation for Erythropoietin. The minimal detectable concentration of  rhu EPO was 20 pg mL-1, which corresponded to 80 pg mL-1 EPO in serum  (serum diluted 1:4). The assay is easy to use, rapid, reproducible and  quantitative, specific and sensitive to measure EPO content in serum  samples.
Keywords: Conjugate; ELISA; immunization; horse radish peroxidase; polyclonal antibody; recombinant human erythropoietin